M2 Macrophages Promote Collagen Expression and Synthesis in Laryngotracheal Stenosis Fibroblasts. (17th August 2020) - Motz, Kevin; Lina, Ioan; Murphy, Michael K.; Drake, Virginia; Davis, Ruth; Tsai, Hsiu‐Wen; Feeley, Michael; Yin, Linda X.; Ding, Dacheng; Hillel, Alexander
Abstract : Objective: Macrophages exhibit distinct phenotypes and are dysregulated in a model of iatrogenic laryngotracheal stenosis (iLTS). Increased populations of alternatively activated or M2 macrophages have been demonstrated. However, the role of these macrophages is unknown. The aims of this study are: 1) define the macrophage population in iLTS in the context of classically activated or M1 and M2 macrophage phenotypes, and 2) characterize the effect of monocyte‐derived M1 and M2 macrophages on normal airway and LTS‐derived fibroblasts (FBs) in vitro. Study Design: Comparative analysis; in vitro controlled study. Methods: Immunohistochemical analysis of human iLTS and control specimens was performed to define the macrophage population. In vitro, M1, and M2 macrophages were polarized using M‐CSF + Interferon‐gamma and lipopolysaccharide or Interleukin‐4, respectively. FBs isolated from laryngotracheal scar (LTS‐FBs) and normal tracheal airway (NA‐FBs) in eight patients with iLTS were cocultured with polarized macrophages. Fibrosis gene expression, soluble collagen production, and proliferation were assessed. Results: Immunohistochemical analysis revealed increased CD11b + cells (macrophage marker) in laryngotracheal scar specimens (18.3% vs. 8.5%, P = .03) and predominant CD206 (M2) costaining versus CD86 (M1) (51.5% vs. 9.8%, n = 10, P = .001). In vitro, NA‐FBs cultured with M2 macrophages demonstrated a 2.41‐fold increase in collagen‐1 expression ( P = .05, n = 8) and an increase in soluble collagen (9.98 vs. 8.875, mean difference: 1.11 95%, confidence interval 0.024–2.192, n = 8, P = .015). Conclusion: Increased populations of CD11b cells are present in iLTS specimens and are predominantly CD206+, indicating an M2 phenotype. In vitro, M2 macrophages promoted collagen expression in airway FBs. Targeting macrophages may represent a therapeutic strategy for attenuating fibrosis in iLTS. Level of Evidence: NA Laryngoscope, 131:E346–E353, 2021